Effect of specific deep cervical muscle exercises on functional disability, pain intensity, craniovertebral angle, and neck-muscle strength in chronic mechanical neck pain: A randomized controlled trial - Thavatchai Suvarnnato (2019)
© 2019 Suvarnnato et al. Background: Exercise is known to be an important component of treatment programs for individuals with neck pain. The study aimed to compare the effects of semispinalis cervicis (extensor) training, deep cervical flexor (flexor) training, and usual care (control) on functional disability, pain intensity, craniovertebral (CV) angle, and neck-muscle strength in chronic mechanical neck pain. Methods: A total of 54 individuals with chronic mechanical neck pain were randomly allocated to three groups: extensor training, flexor training, or control. A Thai version of the Neck Disability Index, numeric pain scale (NPS), CV angle, and neck-muscle strength were measured at baseline, immediately after 6 weeks of training, and at 1- and 3 -month follow-up. Results: Neck Disability Index scores improved significantly more in the exercise groups than in the control group after 6 weeks training and at 1- and 3-month follow-up in both the extensor (P=0.001) and flexor groups (P=0.003, P=0.001, P=0.004, respectively). NPS scores also improved significantly more in the exercise groups than in the control group after 6 weeks’ training in both the extensor (P<0.0001) and flexor groups (P=0.029. In both exercise groups, the CV angle improved significantly compared with the control group at 6 weeks and 3 months (extensor group, P=0.008 and P=0.01, respectively; flexor group, P=0.002 and 0.009, respectively). At 1 month, the CV angle had improved significantly in the flexor group (P=0.006). Muscle strength in both exercise groups had improved significantly more than in the control group at 6 weeks and 1- and 3-month follow-up (extensor group, P=0.04, P=0.02, P=0.002, respectively; flexor group, P=0.002, P=0.001, and 0.001, respectively). The semispinalis group gained extensor strength and the deep cervical flexor group gained flexor strength. Conclusion: The results suggest that 6 weeks of training in both exercise groups can improve neck disability, pain intensity, CV angle, and neck-muscle strength in chronic mechanical neck pain. Trial registration: NCT02656030.